Societies in transition : economic, political and security transformations in contemporary europe - Katsikides, Savvas; Koktsidis, Pavlos I. (Springer International Publishing : Imprint: Springer, 2015)
This edited volume discusses critically the social implications of current structural transformations in Europe within the broader context of the global financial crisis. Experts from across Europe and the US discuss challenges and solutions to political and economic stability, security, growth, governance and integration on a country and regional level, especially focusing on vulnerable Southern and Eastern European states. New economic, political and security processes and realities are examined closely, with the aim to describe them in a coherent framework. Drawing on carefully selected interdisciplinary research, this collection offers fresh insights into the social repercussions of the transition from traditionally established practices and perceptions to new forms of collaboration, integration and governance.